DAMPAK MOTIVASI BELAJAR DAN LINGKUNGAN SEKOLAH TERHADAP PRESTASI BELAJAR DI SDN 45 TALAGA ENREKANG - Syamsidar, Syamsidar (Universitas Negeri Makassar, 2023)
This study aims to find out: (1) Is there any influence of learning motivation on the achievement of social sciences at SDN 45 Talaga (2) Is there any influence on the achievement of social sciences learning at SDN 45 Talaga (3) Is there any influence of learning motivation and school environment together on the achievement of learning Social Sciences (IPA) at SDN 45 Talaga. This study uses correlational with descriptive quantitative approach. The samples in this study were grade IV, V and VI students who numbered 28 students. Sampling technique is by Purposive Sampling technique with participant criteria. This research data was collected through observations, interviews, and documentation. The results showed that: (1) There was no significant influence between learning motivation and IPA learning achievement of learners with rhitung correlation coefficient of 0.195. The apostate value with the amount N = 28 at the error level of 5% is 0.374. Judging from the acquisition of the price r known that 0.195 < 0.374 or rhitung < rtabel, From the data obtained a coefficient of determination (R Square) of 0.038. (2) There is no significant influence between the school environment and students' IPA learning achievement with a correlation coefficient of -0.088. The table r value with the amount N=28 at the 5% error level is 0.374. This indicates that r counts negative and is smaller than table r (-0.088 < 0.374). From the data obtained coefficient of determination (R Square) of 0.008. (3) There is no significant influence between the motivation of learning and the school environment of students' IPA learning achievements. with the correlation coefficient being 0.213. This shows a low influence while the simultaneous contribution of motivational variables and school environment to IPA learning achievement is 4.5%.Penelitian ini bertujuan untuk mengetahui: (1) Pengaruh motivasi belajar terhadap prestasi belajar Ilmu Pengetahuan Alamdi SDN 45 Talaga (2) Pengaruh lingkungan sekolah terhadap prestasi belajar Ilmu Pengetahuan Alam di SDN 45 Talaga (3) Pengaruh motivasi belajar dan lingkungan sekolah secara bersama-sama terhadap prestasi belajar Ilmu Pengetahuan Alam (IPA) di SDN 45 Talaga. Penelitian ini menggunakan pendekatan kuantitatif deskriptif. Sampel dalam penelitian ini adalah peserta didik kelas IV, V dan VI yang berjumlah 28 orang peserta didik. Teknik pengambilan sampel adalah Purposive Sampling dengan kriteria peserta. Data penelitian ini dikumpulkan melalui angket dan dokumentasi. Hasil penelitian menujukkan bahwa : (1) Tidak terdapat pengaruh yang signifikan antara motivasi belajar dengan prestasi belajar IPA peserta didik dengan koefisien korelasi rhitung sebesar 0,195. Nilai rtabel dengan jumlah N = 28 pada taraf kesalahan 5% adalah 0.374. Dilihat dari perolehan harga r diketahui bahwa 0,195 < 0,374 atau rhitung < rtabel, Dari data tersebut diperoleh koefisien determinasi (R Square) sebesar 0,038. (2) Tidak terdapat pengaruh yang signifikan antara lingkungan sekolah dengan prestasi belajar IPA peserta didik dengan koefisien korelasi sebesar -0,088. Nilai r tabel dengan jumlah N=28 pada taraf kesalahan 5% adalah 0,374. Hal ini menunjukkan bahwa r hitung negatif dan lebih kecil dari r tabel (-0,088 < 0,374). Dari data tersebut diperoleh koefisien determinasi (R Square) sebesar 0,008. (3) Tidak terdapat pengaruh yang signifikan antara motivasi belajar dan lingkungan sekolah tehadap prestasi belajar IPA peserta didik. dengan koefisien korelasi adalah 0,213. Hal tersebut menunjukan pengaruh yang rendah sedangkan konstribusi secara simultan variable motivasi dan lingkungan sekolah terhadap prestasi belajar IPA adalah 4,5%.